The Change of Visitor Intention Toward Virtual Reality Using The Theory of The Acceptance Model - Azizah, Aisyah Nur; Cahyadi, Eko Ruddy; Mulyati, Heti (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Virtual Reality (VR) is one of the technologies that has experienced significant growth during Industry 4.0. The total value of tourism-related digital industries is estimated to reach US$210 billion by 2025.Purpose: The purpose of this research is to analyze the factors that contribute to VR usage with the Extended Technology Acceptance Model and to analyze changes in the usage intention of VR.Design/methodology/approach: The factors contributing to the utilization of VR in this study can be analyzed using the Extended Technology Acceptance Model (TAM) approach through Structural Equation Modeling Partial Least Squares (SEM-PLS) analysis. The sample of this study was 115 respondents who had visited Malang Night Paradise and showed an interest in Adventure Land, which offered the use of VR.Findings/result: This study revealed that several factors affecting the changes in the usage intention of VR are identified from the change in the hypothesis of perceived usefulness, which no longer has an effect on attitude toward using and price willingness to pay. Conclusion: This phenomenon is attributed to a decline in attractiveness, changes in user familiarity with VR, negative experiences, changes in market conditions, and economic fluctuations.Originality/value (state of the art): This study was conducted in 2022 and 2023 to measure changes in the usage intention of VR, given that the modernization of information and communication technology in the current digital era has transformed human interaction with their environments. Keywords: structural equation modelling, partial least squares, technology acceptance model, tourism, usage intention, virtual reality